2020
DOI: 10.1021/acsabm.0c00333
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Spheroids with Chronological Phenotype Shifting To Promote Therapeutic Angiogenesis in Critical Limb Ischemia

Abstract: Therapeutic angiogenesis becomes an essential approach to rescue ischemia and the cell-based therapy facilitates ischemia recovery via stimulation of paracrine signals or replacement of damaged cells. Macrophages participate in multiple processes of tissue repair, and the M1 and M2 phenotypes play distinct roles in the sequential stages of healing initiation, angiogenesis stabilization, and tissue maturation. In this study, macrophage spheroids (MøSs) are proposed to promote therapeutic angiogenesis in critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Ran et al . ( 68 ) have generated macrophage spheroids with chrysin-loaded fibers. These fibers not only can serve as a scaffold, but also can release chrysin for regulating the phenotypic transformation of macrophages from pro-inflammatory M1 to anti-inflammatory M2.…”
Section: Critical Limb Ischemia Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Ran et al . ( 68 ) have generated macrophage spheroids with chrysin-loaded fibers. These fibers not only can serve as a scaffold, but also can release chrysin for regulating the phenotypic transformation of macrophages from pro-inflammatory M1 to anti-inflammatory M2.…”
Section: Critical Limb Ischemia Repairmentioning
confidence: 99%
“…In vivo results have revealed that M2 macrophage polarization of spheroids can induce a full recovery of hind-limb ischemia to normal limbs. It has been also proven that macrophage spheroids transplantation can lead to greater limb salvage than single macrophage administration ( 68 ).…”
Section: Critical Limb Ischemia Repairmentioning
confidence: 99%
“…The use of spheroids is currently under investigation for many cell types. To improve the therapeutic effect of cell spheroids even further, various biomaterials (e.g., fibers and hydrogels) have been developed for spheroid engineering [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Note that hydrogels, as artificial 3D cell scaffolds, have attracted great attention in recent years because of their ability to reproduce the biological environment, with their inherent biochemical and physicochemical properties, such as cell adhesion, degradation, and viscoelasticity ( Figure 1 ) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%